POLA PEMBERDAYAAN MASYARAKAT KOTA: KOMPARASI KOTA BANDUNG DAN KOTA KOBE- JEPANG - Puspa Mirani Kadir (Fakultas Komunikasi, Sastra, dan Bahasa, 2018)
Communities in particular cities cannot survive without taking care of their members’ welfares. Therefore, the community’s social workers in several cities have made various efforts to overcome social problems such as the low levels of children's education and the problem of aging society. Some communities, particularly in urban areas, are founded to empower their people. One of urban cities in Indonesia which actively empower its people is Bandung. Relying on professional systems, Bandung strengthens the empowerment of local communities based on the values of togetherness, social moral/ethics, honesty, and mutual trust as well as highlighting its culture. This togetherness value is called in Indonesian as gotong royong. Similar idea has been used by a city in Japan, Kobe. Using a term called sougo fujo, it comprises the idea of togetherness to empower Japanese society. This research aims to compare the ideas of gotong royong and sougo fujo. By comparing social empowerment systems in developed countries like Japan, it will broaden the horizons of value orientation in our country. Similar to communities in Bandung, Kobe communities use their local wisdom to solve their social problems and empower their people. These ideas show that communities’ empowerment can be conducted by engaging the value of togetherness from their members.